Pengaruh Desain Kemasan Dan Persepsi Kualitas Produk Terhadap Keputusan Pembelian Pada Booth Kopi Nescafe (Studi Kasus Pada Generasi Z Di Tasikmalaya) - Reza Silvia Az Zahra; Ardhiansyah Ardhiansyah (Journal Economic Management and Business, 2026)
This study aims to analyze the influence of packaging design and product quality perception on purchasing decisions at Nescafé coffee booths among Generation Z in Tasikmalaya. The research is motivated by increasing competition in the instant coffee industry and the decline in Nescafé’s Top Brand Index, indicating changes in consumer preferences. This study uses a quantitative approach with a survey method involving 100 respondents selected through purposive sampling. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination with IBM SPSS. The results indicate that packaging design has a positive and significant effect on purchasing decisions with a significance value of 0.000 < 0.05. Meanwhile, product quality perception does not significantly affect purchasing decisions with a significance value of 0.772 > 0.05. Simultaneously, both variables contribute 63% to purchasing decisions.